Transformation of Murabahah Financing Orientation During the Covid 19 Pandemic - Aisyah Nurhayati; Moh. Abdul Kholiq Hasan; Imron Rosadi; Andri Nirwana AN (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study was to examine the effect of pandemic covid 19 on the transformation of Murabaha financing orientation in BPRS Dana Amanah Surakarta year 2019-2021. The primary source of this study is a report of data of Murabaha financing in BPRS Dana Amanah Surakarta in 2019-2021 and the interview results. This research uses the content analysis method to identify changes in the orientation of the Murabaha contract during the pandemic. The result of this study is that there is a significant change in the direction of Murabaha financing at BPRS Dana Amanah Surakarta from non-syndicated financing to syndicated financing, and there is a decrease in the number of Murabaha contract transactions. Internal factors and external factors influence these changes. Internal factors there are (1) prudential principle, (2) the company's bridging strategy to maintain bank performance, and external factors are COVID-19 pandemic and the social distancing policy (PSBB).